Towards the development of agricultural extension service policy: initial inputs from agricultural agencies - Abu Hassan, Musa; Bakar, Basri; A. Manan, Junainah; Mohamed Ghazali, Ainul Mardhiyyah; Mohd Yassin, Jamaliyah; Tajuddin, Zaidi (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
In bringing about development into the farming community, agricultural extension service plays an important role. There are three major components of agricultural extension services. First, the agricultural agencies which are responsible in developing the agricultural knowledge, practices and technologies. Second, are the agricultural extension agents who are responsible in imparting and teaching these knowledge, practices and technology to the farmers? Third, the farmers who have their own cultures, values and priorities that may easily accept these knowledge, practices and technologies in their agricultural enterprises, or otherwise. The purpose of this study is to solicit the opinion of agricultural extension agents on the need to have a policy regarding agricultural extension services, the reasons for such necessity and the factors that ought to be considered in the policy formulation. This research was conducted using focus group interview. Three major agricultural development agencies were involved. Findings from the focus group interviews revealed that the extension agents would like to have an extension service policy that would facilitate the agricultural development among the farmers, even though there are clear job specifications for them to conduct their duties. They also suggested some concerns that should be emphasized in developing the extension service policy.